PENERAPAN MODEL PEMBELAJARAN PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAMS GAMES TOURNAMENT TERHADAP MINAT BELAJAR MATEMATIKA SISWA KELAS V SDN 19 SITIUNG - rara rara ariana; Nisa Ratul Janah; Salmi Nur Inayah (Jurnal Dharma PGSD, 2025)
This study aims to determine the interest in learning mathematics of fifth grade students in the second semester of the 2025 academic year at SDN 19 SITIUNG. This study can help improve the interest in learning mathematics of fifth grade students at SDN 19 SITIUNG by using the Cooperative Learning method of the Teams Games Tournament (TGT) type. This study found that there were problems that occurred due to the lack of interest in learning mathematics in fifth grade students at SDN 19 SITIUNG. The researcher found a solution to increase students' interest in learning by using the Team Games Tournament (TGT) model because this model is one of the models that is easy to apply in learning, this research method uses Classroom Action Research (CAR) and the researcher's data collection technique uses Descriptive Statistics analysis